Protección del racimo de plátano (Musa spp) con diferentes números de corbatines en la variedad barraganete - Cedeño Mieles, Dunia Mariela (2013)
With the aim of analyzing the banana variety protection barraganete neckties in different numbers, we made a field investigation using a completely randomized design with 4 treatments and 4 replications using three two one tie plus a control. The results indicate that statistical significance was determined in all the variables under study being the two neckties in bunch weight which presented the highest value with 18.35 Kg for the variables number of hands , degrees of second hand last grade hand over hand along second last hand was determined statistical significance, while the variable quality clusters was the best treatment, the three neckties which present the highest quality cluster with average 96.18 % , were statistically higher than the other treatments . A bowtie treatments and the control showed lower values with 85.66 and 82.02 % respectively. These results demonstrate that the use of corbatines greatly helps to protect the quality of the cluster, as in the banana crop . All study treatments responded positively to the use of the bowtie and these help to better protection and banana bunch quality which is reflected in the research that was carried out on the farm in the San Nicolas area Buena Fe , Province of Los Ríos , Km.20 Quevedo Via Santo Domingo De Los Tsachilas